"Zweckoptimismus" and the Paris process will not save the world from climate catastrophe. (15th February 2018) - Clémençon, Raymond
ABSTRACT: Politicians, government officials, business representatives, and nongovernmental climate activists all in various ways emphasize what they see as progress being made in the aftermath of the Paris Agreement, even if they continue to warn of the dire consequences of business as usual. Indeed, there is no lack of encouraging private and public sector initiatives on climate change. Some macro trends seem to be moving in the right direction, as well. But, closer scrutiny shows that these positive trends are still far from adding up to the necessary fundamental shift in the global energy economy. Furthermore, the public may greatly overestimate the advancement of renewable solar and wind energy technology, which contributes to a false sense of progress and lessens political urgency. Without determined and reinvigorated political leadership from the European Union (EU), there is little hope that necessary emission reduction goals to stay below 2 °C above preindustrial levels can be met. The EU has driven international climate policy from the beginning of climate negotiations, and there is unfortunately no other source of leadership in sight. It will require difficult political decisions to be taken sooner rather than later to force a much quicker domestic energy transition and to raise financing to help developing countries with their own energy transition and adaptation to a rapidly warming world. Integr Environ Assess Manag 2018;14:198–201. © 2018 SETAC Key Points: The Paris Agreement is a noteworthy achievement compared with languishing international negotiations in other areas, but its only legally binding provision is a commitment to a process to review and revise the adequacy of the voluntary nationally determined commitments. By the end of 2016, solar and wind contributed only about 1% of the world's total primary energy consumption and 5.5% of the world's total electricity consumption, significantly below public perception. A massive mobilization of resources is needed to help developing countries leapfrog into the green energy transition and grow their economies sustainably.